Monitoreo de la Deforestacion en las Provincias de Huallaga, el Dorado y Lamas ; en el departamento de San Martin - Reategui Reategui, Alex Mark (2004)
The present thesis, "Monitoreo ofthe Deforestation in the provinces ofHuallaga, the Gilded one and You lick in the Department ofSan Martín", is oriented to contribute with the planning of the occupation of the territory and the use of the natural resources, in special with the process of Ecological and Economic Zonificación of the Region San Martín who the Institute of Investigations of the Peruvian Amazonía and the Regional Government of San Martín come promoting in our region. This work was made in arder to identify and to quantify the advance of the deforestation in the natural forests in the provinces of Huallaga, the Gilded one and You lick, in the department of San Martín; by means of the use of space indicators of the changes in the forest cover, using the Systems of Remate Perception (Teledetección) and the GIS (SIGs), as well as to identify and/or to describe the socioeconomic processes that detennine such process, besides to identify as it is the tendency of the advance of the deforestation in the area of intluence ofthe study. For the analysis it was used images of satellite Landsat TM5 and Landsat TM7, that date from the year of 1986 and 1999. These images were, previously corrected geometrically and treated specially for their later analysis. The analysis was visual optician or (digital format) directly of the screen using images in format of paper like support for the characterization of the units. For the field verification a fast sounding was made, registering sorne types of cover and Earth use in conventional photographies. The results are presented/displayed in images of satellite and maps of changes of the vegetal cover and patterns of use of the Earth as well as in maps of deforestation, for both years and map of evolution ofthe deforestation in a lapse of 13 years. One includes pictures and graphs as well as a matrix of changes those that facilitate the interpretation of the results. The study area, this conformed by the province of Huallaga that has a surface of 236.126 you have and it is located in the central and western part of the Region San Martín and almost occupies the totality of the river basin of the Saposoa river and the high river basin of the Huayabamba river; the province of the Gilded one that has a surface of 131.933 you have and it is located in the North and Western part of the Region San Martín; and the province of You lick that it has a surface of 501.056 you ha ve and is located in the North part of the Region San Martín. These three provinces altogether have a surface of 869.115 you have what represents 17,23 % of the territory of the Region. The economic base of this territory is the agriculture of subsistence, cattle ranch and the forest activity. lt was gotten to determine that the surface deforested in the provmce of Huallaga, in the lapse of the time of study, was of 30.440,92 you ha ve, with an annual rate of 1,64%, and mainly with farming aims, it is to say; subsistence agriculture (29.63%); in the province of the Gilded one, it was of 14.807,03 you have, with an annual rate of 1,54%, and also with aims of subsistence (54.77%); whereas in the province of You lick the intervention was of 41.889,96 you have, being 32,48% with farming aims, registering an annual rate of only 0.90%. These processes are fundamental consequence of one disordered occupation of the territory. The common denominator in the three provinces that form the study area is that, the deforestation pattem is massive or mosaic type in the zones of greater population and sorne zones where limitantes physicists exist or where the population is Iittle, the deforestation pattem is of linear type; in addition their economies are sustained in the subsistence agriculture, that includes bread cultures fundamentally to take (maize, frijol, rice, yucca, banana), complemented with agro-industrial cultures ( coffee, cacao, tobacco), fiuit trees (citric, papaya, fragmentation hand grenade), among others. Another activity is the cattle ranch that is carried out applying only sorne techniques essential to manage to maintain an suitable Earth use by lack of arboreal cover, giving rise to that the grounds, which they are highly vulnerable, are exposed to sorne way of erosion, impoverishment, risk of tloods in sorne cases, among others. And finally we have the forest activity like is the wood extraction, that is not considered like inaintained economy since at the present time this heading does not count on an ~luation of the logable volume to lack forest inventaries, since in lands of forest ap~itude and protection at the moment they are occupied in its majority by agricultura! activities. Two future scenes have been analyzed. In the tendencial scene it is anticipated, rhat to continue the same rate of deforestation of last the 13 years, the province of Huallaga will be of forestada in 40 years approximately, the province of the Gilded one in 09 years and the province of You tick approximately in 60 years, worsening the conditions of poverty, the loss of biodiversity and in general still more the environmental problems. However in scene wished, that it implies the ordered process of the occupation of the territory of the three provinces that cover the area with study, esteem that the intervention will be made only in areas with farming vocation, and in the areas with forest vocation projects of sustainable forest handling will be being been developing; in addition it is also anticipated that in this one scene it is managed to trigger a process of sustainable development, is increased the Earth productivity, improves the well-being of the population, the biological diversity is conserved and the atmosphere is preserved. The implementation is recommended in addition to a plan of territorial ordering for each one of the provinces that conform the study area, with base in the Ecological and Economic Zonificación of the Region San Martín; as well as to make the monitoreo of the deforestation at least every two years, in order to come up or to mitigate, according to is the case, the negative effects of the deforestation process.